The Hematopoietic Differentiation and Production of Mature Myeloid Cells from Human Pluripotent Stem Cells - Choi, Kyung-Dal (2011)
Here we describe a protocol for hematopoietic differentiation of human pluripotent stem cells (hPSCs) and generation of mature myeloid cells from hPSCs through expansion and differentiation of hPSC-derived lin-CD34(+)CD43(+)CD45(+) multipotent progenitors. The protocol is comprised of three major steps: (i) induction of hematopoietic differentiation by coculture of hPSCs with OP9 bone marrow stromal cells, (ii) short-term expansion of multipotent myeloid progenitors with a high dose of GM-CSF, and (iii) directed differentiation of myeloid progenitors into neutrophils, eosinophils, dendritic cells (DCs), Langerhans cells (LCs), macrophages, and osteoclasts. The generation of multipotent hematopoietic progenitors from hPSCs requires 9 days of culture, and an additional 2 days are needed to expand myeloid progenitors. Differentiation of myeloid progenitors into mature myeloid cells requires an additional 5–19 days of culture with cytokines, depending on the cell type.